Combustion of Straw Pellets in an Agitated Fuel Bed: Experiments and DEM/CFD Simulations. Issue 1 (2nd January 2022) - Buss, F.; Wirtz, S.; Scherer, V.
ABSTRACT: The influence of bed agitation during the combustion of biomass pellets was investigated experimentally and numerically. In the experiments, a bulk of straw pellets was burnt in a batch-operated reactor. The reactor allows for air staging and mixing of the fuel bed by vertically moveable mixing elements. The primary to secondary air ratio was varied and the reactor was operated either in the agitated (moving mixing elements) or the static mode (mixing elements at rest). The overall mass of the bulk was measured continuously during the combustion process. The results show a significant increase of the mass loss rate by almost 60% when the bed was agitated compared to the static case. Samples of the residual material of the pellets reveal a totally different amount of molten and agglomerated ash particles for the different operational conditions. Decreased primary to secondary air ratios as well as agitation of the fuel bed did lead to less agglomeration of the ash. The Discrete Element Method (DEM) was coupled with a Computational Fluid Dynamics (CFD) simulation. Coupled DEM/CFD simulations of the batch reactor were performed to get access to bulk internal data of the solid material and the fluid phase. Simulations identified that a reduced amount of ash exposed to the volatile flame through agitation of the fuel bed was the main reason for minimized ash agglomeration.